Policy in Practice: A Systematic Review of WCAG 2.2 and ADA 2024 Effects on Web and Mobile Accessibility - Purwandari, Nuraini; Dewi, Ratna Kusuma; Rinaldo; Sucipto, Purwo Agus (Digitus : Journal of Computer Science Applications, 2025)
Digital accessibility remains a global concern, affecting 1.3 billion people with disabilities. This study evaluates the impact of two policy changes WCAG 2.2 and the 2024 ADA Final Rule on digital interface compliance. A systematic review was conducted using PRISMA 2020 guidelines. Data were sourced from academic databases and regulatory documents spanning 2015–2024. Studies were selected based on their relevance to WCAG/ADA compliance. Quality appraisal was carried out using the Mixed Methods Appraisal Tool (MMAT), and findings were synthesized narratively across web and mobile contexts. WCAG 2.2 added success criteria to improve usability for users with cognitive, motor, and visual impairments. ADA 2024 requires U.S. public sector platforms to meet WCAG 2.1 AA, while the European Accessibility Act shows uneven implementation among member states. WebAIM’s 2024 audit revealed that 95.9% of websites still fail basic accessibility checks, and mobile platforms show even lower compliance. Common issues include poor contrast, missing alt text, and inadequate touch targets. Automated tools alone are insufficient without assistive technology validation. Over reliance on ARIA, limited developer training, and inconsistent policy enforcement persist as barriers to effective implementation. Regulatory updates represent progress but must be supplemented by education, standardized testing protocols, and user involved design practices. Sustainable accessibility requires a shift from reactive compliance to proactive inclusivity, supported by policy, pedagogy, and participatory design.